Advancement in Rural Digital Infrastructure: Charting the Way Forward for Digital Agriculture - Kumar, Shalander; Rupavatharam, Srikanth; Patil, Mukund; Kumar, Kishore G.; Jat, Mangi L. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
ICRISAT, in collaboration with ICAR and NAAS, hosts two-day conference on Digital Agriculture to shape strategic roadmap for the sector. ICRISAT recently held a two-day National Conference on "Digital Agriculture: Empowering Indian Farming" in collaboration with the Indian Council of Agricultural Research (ICAR) and National Academy of Agricultural Sciences (NAAS) at the A.P. Shinde Symposium Hall, New Delhi. The conference, held from 17 to 18 December 2024, brought together a vibrant community of thought leaders, practitioners, policymakers, researchers, and industry stakeholders focused on charting the future course of digital agriculture in India by leveraging advancements in rural digital infrastructure.